Are they out to get me? Individual differences in nonclinical paranoia as a function of narcissism and defensive self‐protection. Issue 5 (20th December 2021) - Hepper, Erica G.; Ellett, Lyn; Kerley, Danielle; Kingston, Jessica L.
Abstract: Objective: Three studies tested a novel model of the narcissism‐paranoia link, whereby narcissism (primarily its socially maladaptive facets) is associated with paranoia via over‐use of defensive self‐protection and/or under‐use of self‐affirmation. Methods: In Study 1, 245 online volunteers (87% female; M AGE = 20.92; 44% White‐British) completed trait measures of narcissism, self‐enhancement/protection strategies and paranoia. In Study 2, 116 students (82% female; M AGE = 20.23; 70% White‐British) completed baseline measures, then reported state reactions and paranoia following two difficult and two pleasant interpersonal events after 3–10 days. In Study 3, 517 online volunteers (64% female; M AGE = 22.76; 77% White/Caucasian) completed baseline measures, experienced a standardized social exclusion (vs. neutral) manipulation (Cyberball), then reported state reactions and paranoia. Results: In Study 1, narcissism was associated with higher paranoia via defensiveness. In Study 2, this was replicated in difficult but not pleasant events, and was driven by the Entitlement/Exploitativeness facet of narcissism. In Study 3, narcissistic rivalry and vulnerable narcissism, but not admiration, were associated with Cyberball‐related paranoia via general defensiveness and denigration of others. Conclusions: Individuals high in narcissism—especially its socially maladaptive facets—who over‐rely on defensive self‐protection strategies in response to threat, are particularly vulnerable to paranoia. Findings help to understand individual differences in paranoia.